OPTIMALISASI PEMASARAN DIGITAL UNTUK MENINGKATKAN DAYA SAING UMKM DI DESA SASAHAN - Susanto, Denies; Ridwan, Ade (Yayasan Education and Social Center, 2024)
This Community Service Activities aims to overcome the challenges faced by Micro, Small and Medium Enterprises (MSMEs) in Sasahan Village related to limited market reach and competitiveness. This Community Service focuses on introducing and training MSMEs in utilizing digital marketing strategies to expand market reach and increase their competitiveness. This activity includes workshops, coaching sessions, content development assistance, and performance evaluations to empower MSMEs to adopt digital marketing strategies effectively. Collaboration with local governments, MSME associations, digital marketing experts and communities ensures comprehensive and sustainable support. Through this community involvement initiative, we aim to increase the economic prosperity of Sasahan Village by empowering its MSMEs to develop and be competitive in the digital era